Hubungan Antara Komunikasi Efektif dengan Kualitas Pelayanan di Rumah Sakit Islam Sultan Agung Semarang - Husnul Mubarok; Dyah Wiji Puspita Sari; Retno Issroviatiningrum (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Background: Effective communication is an essential element in patient-centered healthcare, as it functions to build trust, reduce anxiety, and improve patient adherence to the treatment plan. However, communication gaps between healthcare providers and patients are still found, which can negatively impact treatment success and patient satisfaction. A preliminary study at RSI Sultan Agung Semarang showed that 80% of respondents stated they were satisfied with the communication and quality of services provided, making this research important to deeply examine the relationship between the two variables. Objective: This study aims to analyze the relationship between effective communication and the quality of services perceived by hospitalized patients at Rumah Sakit Islam Sultan Agung Semarang. Method: This research used an analytical observational design with a cross-sectional approach and a quantitative research type. The independent variable studied was effective communication and the dependent variable was service quality. The total number of respondents in this study was 118 people. Data were collected using questionnaires and analyzed using the Spearman’s rho correlation test to examine the relationship between variables. Results: The results of the bivariate analysis using the Spearman’s rho test indicated a significant relationship between effective communication and service quality. A correlation coefficient (ρ) value of 0.515 was obtained with a significance value of p = 0.000 (p < 0.05).